THE TOOLS OF OPTOMISATIOM THE SELF-STYDY WITH THE PHILOLOGY STUDENTS - Koknova, Tetyana A. (Educological discourse, 2015)
The article reveals ways of optimization of the self-study while teaching the prospective philologists’; the essence of the independent work with the students during training in the high school is highlighted; the training strategies for students are defined in the performance of the self-study; types of control are characterized during the self-study that can orient lectures of the specialized disciplines to implement pedagogical innovations in the training of philology students.